2020
DOI: 10.3390/ijerph17197043
|View full text |Cite
|
Sign up to set email alerts
|

Electrocochleography in Cochlear Implant Users with Residual Acoustic Hearing: A Systematic Review

Abstract: (1) Objectives: This study reviews the use of electrocochleography (ECoG) as a tool for assessing the response of the peripheral auditory system and monitoring hearing preservation in the growing population of cochlear implant (CI) users with preserved hearing in the implanted ear. (2) Methods: A search was conducted in PubMed and CINAHL databases up to August 2020 to locate articles related to the ECoG measured during or after the cochlear implant (CI) surgery for monitoring purposes. Non-English articles, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
0
13
0
1
Order By: Relevance
“…This would suggest that relatively small differences in baseline hearing heavily influence a screening tool's performance. Alternatively, there is a growing body of evidence that suggests traditional audiometric thresholds and WRS do not accurately reflect the health of the cochlea or central processing skills that may be utilized as surrogate markers for CICE (29)(30)(31)(32)(33). Therefore, differences in performance on external validation could be attributed to factors not currently being captured by routine audiograms.…”
Section: Discussionmentioning
confidence: 99%
“…This would suggest that relatively small differences in baseline hearing heavily influence a screening tool's performance. Alternatively, there is a growing body of evidence that suggests traditional audiometric thresholds and WRS do not accurately reflect the health of the cochlea or central processing skills that may be utilized as surrogate markers for CICE (29)(30)(31)(32)(33). Therefore, differences in performance on external validation could be attributed to factors not currently being captured by routine audiograms.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, ANN/SUM amplitudes measured in those studies showed no statistically significant attenuation with simultaneous ES ( Koka and Litvak, 2017 ; Krüger et al, 2020b ). ANN is phase-locked activity evoked by low-frequency AS ( Kim, 2020 ). Therefore, at medium-high frequencies acoustic tests, ANN performs poorly.…”
Section: Discussionmentioning
confidence: 99%
“…The quality assessment of the case series included in this guide was assessed with the National Institutes of Health (NIH) Study Quality Assessment Tool for Case Series Studies. Each study’s summary score was calculated as a percentage with four scoring categories: (1) poor, 0–25%; (2) fair, 26–50%; (3) good, 51–75%; and (4) excellent, 76–100% ( Kim, 2020 ).…”
Section: Methodsmentioning
confidence: 99%